Sanksi Denda Uang bagi Pelanggar Peraturan dalam Perspektif Hukum Islam: Studi Kasus Penerapan Peraturan Asrama Putri Ma'had Al Ishlah Maros Tahun 2019-2020 - Riska, Riska; Farida Aprianti; Muqnitah, Muqnitah; Awal Rifai (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
The application of monetary penalties as a disciplinary measure in Islamic law has sparked diverse scholarly debates, particularly regarding its validity and conditions for implementation. This study examines the regulations and enforcement of monetary penalties at the female dormitory of Ma’had Al-Ishlah Maros during 2019–2020, aiming to analyze their alignment with Islamic jurisprudence. The primary research questions address (1) the rules and practices surrounding monetary penalties in the dormitory and (2) the Islamic legal perspective on their implementation. This research employs a qualitative field study (Field Research) with a case study approach. Data collection methods include observation, interviews, and documentation, analyzed through normative theological and sociological perspectives. The findings reveal that monetary penalties were applied in three administrative domains: language, cleanliness, and memorization (tahfīẓ), based on a verbal consensus between the dormitory administrators and students. In Islamic jurisprudence, the discourse on monetary penalties is divided: some scholars permit it under judicial authority for public welfare, while others, upheld by the majority (jumhūr), categorically prohibit it, citing the principle of safeguarding Muslim property and avoiding unjust enrichment. Fatwa from Lajnah Daimah supports the prohibition of monetary penalties imposed without legitimate religious authority, even when agreed upon consensually. This study contributes to the discourse on disciplinary measures in Islamic educational settings by exploring the tension between contemporary practices and classical jurisprudence. It highlights the need for further refinement of disciplinary frameworks in Islamic boarding schools to ensure compliance with Shariah principles and foster ethical governance.